БЕРДАҚТЫҢ ТАРИЙХЫЙ – ЭПИКАЛЫҚ ШЫҒАРМАЛАРЫНДА РУЎ – ҚӘЎИМЛЕР ТАРИЙХЫНЫҢ ГЕЙПАРА МӘСЕЛЕЛЕРИ - Утамбетова, А.Ж. (FAN va JAMIYAT, 2020)
The article deals with the historical and epic works of Berdakh, including the etymology of the history of the origin of the Karakalpak tribal communities in the dastan «Shejire» («Genealogy»). The history of the tribal communities not only indicates their kinship, but also the peculiarities of each kind. The achievements of some of them at the state level, even the ulus, the author concludes that the Karakalpak people are brave and courageous people, consisting of powerful family tribal communities.